Gender Differentials of Metabolic Syndrome in Bangladesh taking Menopause into Consideration - Billah, Syed Muhammad Baqui; Jahan, Muna Shalima; Jundi, Saadi Al; Rajab, Ahmad Mamoun (International Journal of Human and Health Sciences (IJHHS), 2020)
Objective:To assess the gender differences of metabolic syndrome (MetS) in Bangladesh and factors associated with it. Materials and methods: Cross sectional study was performed on 227 premenopausal women, 48 menopausal women and 217 men. The gender differentials were studied with measurement of waist circumference, blood pressure and fasting blood for triglyceride (TG), high density lipoprotein (HDL), blood sugar (FBS). Results:Premenopausal women had 22.9% (95% CI: 17.9-28.8%), menopausal women had 43.8% (95% CI: 30.7-57.7%), and the men had 53.9% (95% CI: 47.3-60.4%) prevalence of MetS giving a 1:1.7:2.1 ratio of premenopausal, menopausal women and men prevalence respectively. More than 95% of study population had low HDL irrespective of gender and menopause status. Obesity was 5.3% in premenopausal women, 14.6% in menopausal women and 54.4% in men. HTN was 10.6% in premenopausal women, 35.4% in menopausal women, and 19.4% in men. High TG was 42.5% in premenopausal women, 41.7%, in menopausal women and 62.0% in men. High FBS was 22.0% in premenopausal women, 37.5% in menopausal women and 30.4% in men. Conclusion: Compared to premenopausal women, MetS in men was two times higher and nearly two times higher in menopausal women, pulling menopausal women prevalence almost equal to men. Menopausal women had high prevalence of HTN while obesity was more prevalent in men. Dyslipidemia should be a concern for the policy makers in search of a prevention program. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 101-107